2021
DOI: 10.48550/arxiv.2104.08323
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Random and Adversarial Bit Error Robustness: Energy-Efficient and Secure DNN Accelerators

Abstract: Deep neural network (DNN) accelerators received considerable attention in recent years due to the potential to save energy compared to mainstream hardware. Low-voltage operation of DNN accelerators allows to further reduce energy consumption significantly, however, causes bit-level failures in the memory storing the quantized DNN weights. Furthermore, DNN accelerators have been shown to be vulnerable to adversarial attacks on voltage controllers or individual bits. In this paper, we show that a combination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 69 publications
(200 reference statements)
0
1
0
Order By: Relevance
“…Previous studies [20], [53] observed that increasing the network capacity can improve the robustness against the bit-flip based attack. Moreover, the training strategies in [53], [54], [55], [56] can improve the robustness of the model parameters. There exist other works considering defense in the inference stage, such as weight reconstruction-based defense [57], detectionbased defense [58], [59], and Error Correction Codes (ECC)-based defense [60], [61].…”
Section: Weight Attackmentioning
confidence: 99%
“…Previous studies [20], [53] observed that increasing the network capacity can improve the robustness against the bit-flip based attack. Moreover, the training strategies in [53], [54], [55], [56] can improve the robustness of the model parameters. There exist other works considering defense in the inference stage, such as weight reconstruction-based defense [57], detectionbased defense [58], [59], and Error Correction Codes (ECC)-based defense [60], [61].…”
Section: Weight Attackmentioning
confidence: 99%